Analysis of thrust-induced sail plane coning and attitude motion of electric sail. (January 2021) - Du, Chonggang; Zhu, Zheng H.; Li, Gangqiang
Abstract: This paper investigates the dynamic characteristics of thrust-induced sail plane coning and attitude motion of an electric solar wind sail (E-sail) by considering high-order modes of flexible elastic tethers. The tethers of the E-sail are assumed elastic and discretized into inter-connected 2-noded tensile elements using the nodal position finite element method, while the central spacecraft and the remote units are simplified as lumped masses. The E-sail is assumed in the heliocentric ecliptic orbital plane at a distance of 1 au from the Sun. The influences of the propulsive force models and the initial E-sail orientation on the dynamic characteristics of the sail plane coning and attitude motion of E-sail are analyzed. The current work derives an analytic expression of the coning motion frequency under the assumption of small coning angle. Through parametric analyses, the current work shows that the magnitude of the propulsive force significantly influences the increment magnitude of the E-sail's orbital radius while has little effect on the angles of sail and thrust angles and the E-sail spin rate. The parametric analyses also show that the initial E-sail orientation significantly influences the thrust vector and the variation of sail angle. Finally, the relationships of the sail and thrust angles, as well as the dimensionless acceleration of the E-sail, are given in polynomial expressions by curve-fitting of simulation results of E-sails with the consideration of coning motion. The relationships are compared with the previous results of E-sails without including coning motion. It shows the coning motion has negligible effect on the macro dynamic behaviors of E-sail. Highlights: Investigated thrust-induced sail plane coning and attitude motion of E-sail. Considered high-order modes of elastic tethers using nodal position finite element method. Derived analytic expression of frequency of periodic coning motion of sail plane.